Phylogenetic relationships of the bumblebees Bombus moderatus, B. albocinctus, B. burjaeticus, B. florilegus and B. cryptarum based on mitochondrial DNA markers: a complex of closely related taxa with circumpolar distribution. (Hymenoptera: Apidae: Bombus). - Bertsch, Andreas; Hrabé de Angelis, Martin; Przemeck, Gerhard K. H. (Contributions to Entomology = Beiträge zur Entomologie, 2010)
Spring queens of Bombus moderatus from Alaska/USA and Alberta/Canada, and of B. burjaeticus and B. patagiatus from the Russian Transbaikal region were collected at different localities. In addition, males of B. florilegus were collected from Hokkaido/Japan. Partial sequences (length 1005 bp) of mitochondrial cytochrome oxidase subunit I (COI) were sequenced from specimens from each locality and species. For comparison, museum specimens of B. albocinctus and B. burjaeticus were also sequenced. The intraspecific sequence divergence was only 1–2 base substitutions and about 0.001–0.002 in Tamura-Nei genetic distance. The interspecific sequence divergence between B. moderatus, B. albocinctus and B. burjaeticus was only 1–5 base substitutions and about 0.001–0.005 in Tamura-Nei genetic distance, whereas the sequence divergence between B. lucorum, B. magnus, B. patagiatus and B. cryptarum was about 24–44 base substitutions and approximately 0.027–0.042 in Tamura-Nei genetic distance. The MrBayes maximum likelihood tree generated a tree topology with three separate clusters for B. lucorum, B. magnus and B. patagiatus, and one large cluster which united B. albocinctus, B. burjaeticus, B. moderatus and B. florilegus. Because there are no gaps in the alignments of COI sequences, single nucleotide sites were used as positional homologies. Each taxon was characterised by about 8–20 substitutions which were unique (“private”) and could be used as diagnostic characters to define and identify these taxa. An analysis of the number of diagnostic characters confirmed the clustering of the maximum likelihood tree. To bridge the gap of about 5000 km between the most eastern known localities for B. cryptarum in the Caucasus and Elburz Mountains and B. burjaeticus/ B. albocinctus in the Russian Transbaikal region and the Russian Far East, 12 more museum specimens from the Central Asiatic Mountains and the Himalayas were sequenced. By analysing the diagnostic positions in the sequences of this almost 100-year-old museum DNA, it was shown that none were connected with B. lucorum: they all clustered within the cryptarum-complex taxa.